2010
DOI: 10.1152/ajpheart.00878.2009
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent relaxation by G protein-coupled receptor 30 agonists in rat carotid arteries

Abstract: Recent studies have identified that the novel membrane estrogen receptor, G protein-coupled receptor 30 (GPR30), is present in blood vessels. However, the signaling mechanisms associated with GPR30 in the vasculature remain unclear. We examined whether putative agonists of GPR30 exert vasorelaxant and/or antioxidant effects similar to those reported for estrogen. Using wire myography, we assessed the role of the endothelium in relaxation responses to the GPR30 agonists, G-1 and 5408-0877 (1 nM-10 microM), in U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
123
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 37 publications
12
123
0
Order By: Relevance
“…[39][40][41] It has also been reported that stimulation of GPR30 blocks VSMC proliferation. 37,42 The vasodilator action of G-1 may be mediated by NO-independent 40 and NO-dependent 37,39,40 pathways; the latter involves GPR30-induced endothelial NO synthase (eNOS) phosphorylation. 43 Also, G-1 decreases nicotinamide adenine dinucleotide phosphate-stimulated superoxide production by the carotid and intracranial arteries, indicating the scavenging effects of GPR30 on superoxide anions.…”
Section: Action Of Estrogen On the Cardiovascular Systemmentioning
confidence: 92%
See 1 more Smart Citation
“…[39][40][41] It has also been reported that stimulation of GPR30 blocks VSMC proliferation. 37,42 The vasodilator action of G-1 may be mediated by NO-independent 40 and NO-dependent 37,39,40 pathways; the latter involves GPR30-induced endothelial NO synthase (eNOS) phosphorylation. 43 Also, G-1 decreases nicotinamide adenine dinucleotide phosphate-stimulated superoxide production by the carotid and intracranial arteries, indicating the scavenging effects of GPR30 on superoxide anions.…”
Section: Action Of Estrogen On the Cardiovascular Systemmentioning
confidence: 92%
“…43 Also, G-1 decreases nicotinamide adenine dinucleotide phosphate-stimulated superoxide production by the carotid and intracranial arteries, indicating the scavenging effects of GPR30 on superoxide anions. 39 In the heart, G-1 reduces ischemia/reperfusion injury and preserves cardiac function through the phosphatidylinositol 3-kinase/Akt and extracellular signal-regulated kinase pathways and by eNOS phosphorylation. 44,45 Treatment with G-1 for 2 weeks reduced the expression of angiotensin II type 1 receptor and angiotensin-converting enzyme.…”
Section: Action Of Estrogen On the Cardiovascular Systemmentioning
confidence: 99%
“…Xing et al (2007) found that E 2 inhibits TNFa-stimulated expression of the neutrophil-specific chemokine cytokine-induced neutrophil chemoattractant (CINC)-2b and suggested that this effect might be responsible for the reduced infiltration of neutrophils, which is observed in animal models after vessel injury. Finally, estrogens are also known to reduce oxidative stress in VSMC by increasing expression of antioxidative enzymes such as superoxide dismutase and reducing expression and/or activity of NADPH oxidase (Strehlow et al 2003, Wassmann et al 2005, Wing et al 2009, Broughton et al 2010, Sivritas et al 2011. The antiproliferatory, pro-apoptotic, anti-migratory, anti-oxidative, and anti-inflammatory in vitro effects of estrogens collectively translate into reduced neointima formation under in vivo conditions.…”
Section: Short Termmentioning
confidence: 99%
“…More recently, GPR30 was found to be expressed on VSMC and to modulate vascular tone in rats and in isolated human arteries (Haas et al 2009). GPR30 activation was shown to inhibit VSMC proliferation and NADPH oxidase activation, and GPR30 expression was required for the estrogen-mediated VSMC apoptosis (Ding et al 2009, Haas et al 2009, Broughton et al 2010. Hence, GPR30 activation in VSMC may be tentatively added to the list of cellular effects exerted by estrogens, which are considered atheroprotective.…”
Section: Short Termmentioning
confidence: 99%
“…In vivo, GPER activation has been shown to mediate hypotensive effects (15,21), predominantly mediating endothelium-dependent vasorelaxation (2,23), although there is one report of endothelium-independent relaxation (31) and one report of GPER-mediated vasoconstriction (1). Our initial studies demonstrated aldosterone's rapid effects on endothelium-dependent vasodilator mechanisms and endothelial cell MAP kinase regulation.…”
mentioning
confidence: 92%